Rebo Wekasan in Cempakasari: Harmony of Islamic Values and Local Wisdom through Living Qur'an - Tria Umami (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study examines the symbolic meanings inherent in the Rebo Wekasan tradition within the framework of the Living Qur’an in Cempakasari Village, Serang, Indonesia. As a cherished cultural heritage observed on the last Wednesday of Safar in the Hijri calendar, Rebo Wekasan seamlessly blends Islamic values with local wisdom, serving as a communal rite for seeking protection from calamities and invoking blessings. Employing a qualitative ethno-graphic approach, the research draws on participatory observation, in-depth interviews with villagers, and document analysis to unpack how participants interpret ritual symbols—such as collective prayers, almsgiving, and the ritual use of sacred water—as manifestations of Qur’anic principles like tawhid, compassion, and divine safeguarding. The findings reveal that, although not universally practiced in the village, Rebo Wekasan fosters social and spiritual harmony, serving as a dynamic vehicle for transmitting contextual Islamic teachings. It reflects the community's lived interpretation of Qur’anic verses on unity (e.g., surah al-Hujurat [49]: 13) and protection (e.g., surah al-Baqarah [2]: 286), countering misconceptions of syncretism by highlighting authentic integration. Community perceptions highlight its role in preserving cultural identity amid modernization, promoting resilience, and fostering ethical living. Ultimately, this tradition exemplifies how local practices embody the Qur’an’s vitality, bridging anthropology and religious studies to affirm the harmony between faith and folklore in Indonesian Muslim societies.